Realistic Large‐Scale Modeling of Rashba and Induced Spin–Orbit Effects in Graphene/High‐Z‐Metal Systems. Issue 10 (5th August 2018) - Voloshina, Elena; Dedkov, Yuriy
Abstract: Graphene, as a material with a small intrinsic spin–orbit interaction of approximately 1 µeV, has a limited application in spintronics. Adsorption of graphene on the surfaces of heavy metals was proposed to induce the strong spin splitting of the graphene π bands either via Rashba effect or due to the induced spin–orbit effects via hybridization of the valence band states of graphene and metal. Spin‐resolved photoelectron spectroscopy experiments performed on graphene adsorbed on the substrates containing heavy elements demonstrate the "giant" spin splitting of the π states of the order of 100 meV in the vicinity of the Fermi level ( E F ) and the K point. However, recent scanning tunneling spectroscopy experiments did not confirm these findings, leaving the fact of the observation of the "giant" Rashba effect or induced spin–orbit interaction in graphene still open. Thus, a detailed understanding of the physics in such systems is indispensable. From the theory side, this requires, first of all, correct modeling of the graphene/metal interfaces under study. Here, realistic super‐cell density‐functional theory calculations are presented, including dispersion interaction and spin–orbit interaction, for several graphene/high‐Z‐metal interfaces. While correctly reproducing the spin‐splitting features of the metallic surfaces, their modifications under graphene adsorption and doping level of graphene, it is revealed that neither "giant" Rashba‐ nor spin–orbit‐induced splitting of the graphene π states around E F take place. Abstract : The possibility of spin manipulation in 2D systems is a cornerstone of spintronics. Substrate‐induced spin–orbit interaction is one of the ways to lift the spin degeneracy in pure 2D material—graphene. Here, state‐of‐the‐art large‐scale density‐functional theory calculations are used to investigate the properties of graphene adsorbed on high‐Z‐metals with strong spin–orbit interaction.